(untitled) (Tempo e Argumento, 2021)
This article establishes a reflection about one of the most outstanding phenomena of memory vindication regarding the recent past in Uruguay: the “Marches of Silence.” They correspond to one of the main mass expressions linked to memory celebration and vindication concerning this past. A history of them is established, the reason for their origin and development, emphasizing the poetics of memory around this mobilization, taking as an example the initiatives of the “Images of Silence” team (which motivated the author’s exhibition at the IV International Seminar on History of the Present Time). Through the creative proposals of this group, the importance and repercussion of the portraits of prisoners who disappeared in those marches are analyzed, motivated by the projects undertaken by this team of photographers. By means of a series of interviews, press releases, and analysis of what was communicated on the website of the Association of Mothers and Relatives of Missing Prisoners, an investigation is carried out on the use, circulation, and appropriation of these images by the population. Along with the very testimony of those who participate in the marches, the symbolic value of these images was verified through their various uses and unfoldings as a ‘weapon’ of denunciation, vindication, and struggle to keep alive the memory of missing prisoners and with it to prevent such human rights violations from happening again. Keywords: poetics of memory; marches of silence in Uruguay. Images of silence.